Pengaruh Motivasi Dan Kompetensi Terhadap Kinerja Pegawai: Survey pada salah satu instansi pemerintah di Kota Bandung - Syyafiya Rheina Destiana; Nenny Rinawati; Retno Resawati; Windi Matsuko Danasasmita (Acman: Accounting and Management Journal, 2022)
This study aims to determine the effect of motivation and competence on employee performance—the research conducted at one of the government agencies in the city of Bandung. The study used a survey approach to employees with 67 respondents. Researchers used descriptive analysis techniques and verification analysis. The study results indicate that there is a significant influence of motivation and competence on employee performance and the domain of influence is motivation. Furthermore, the study results indicate that to improve employee performance, agencies should give a sense of responsibility to their employees if they do not work carefully; if the employee's work is not done carefully, the agency can reprimand the employee firmly.